2005
DOI: 10.1111/j.1461-0248.2005.00841.x
|View full text |Cite
|
Sign up to set email alerts
|

Slow response of plant species richness to habitat loss and fragmentation

Abstract: We examined the response of vascular plant species richness to long-term habitat loss and fragmentation of Estonian calcareous grasslands (alvars). The current number of habitat specialist species in 35 alvars was not explained by their current areas and connectivities but it was explained by their areas and connectivities 70 years ago (R(2) = 0.27). We estimated the magnitude of extinction debt in local communities by assuming an equilibrium species richness in 14 alvars that had lost only a small amount of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
486
6
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 480 publications
(520 citation statements)
references
References 42 publications
26
486
6
2
Order By: Relevance
“…Studies of temporal dynamics in temperate, open, and seminatural habitats have systematically addressed general patterns of area decrease and isolation increase resulting from habitat fragmentation (Adriaens et al, 2006;Helm et al, 2006;Lindborg and Eriksson, 2004), whereas little attention has been paid to the potential contribution of secondary habitat origins through time (but see Arroyo-Mora et al, 2004;Jacquemyn et al, 2003). Our study demonstrated that spatial changes in wet heathlands, poor fens and bogs spanning the last 250 years resulted from two processes acting jointly: destruction and origin of habitat patches.…”
Section: Spatio-temporal Dynamics Of Habitat Patchesmentioning
confidence: 88%
See 3 more Smart Citations
“…Studies of temporal dynamics in temperate, open, and seminatural habitats have systematically addressed general patterns of area decrease and isolation increase resulting from habitat fragmentation (Adriaens et al, 2006;Helm et al, 2006;Lindborg and Eriksson, 2004), whereas little attention has been paid to the potential contribution of secondary habitat origins through time (but see Arroyo-Mora et al, 2004;Jacquemyn et al, 2003). Our study demonstrated that spatial changes in wet heathlands, poor fens and bogs spanning the last 250 years resulted from two processes acting jointly: destruction and origin of habitat patches.…”
Section: Spatio-temporal Dynamics Of Habitat Patchesmentioning
confidence: 88%
“…Piessens and Hermy (2006) suggested that a low species loss rate in highly fragmented north Belgium heathlands may be the result of an extinction debt, but provided no direct test for this hypothesis. However, some studies in semi-natural grasslands have reported evidence of an extinction debt (Gustavsson et al, 2007;Helm et al, 2006) but other studies have not provided supporting data (Adriaens et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alongside with this trend, a sharp decline of extensive husbandry has occurred in the last decades in favour of more productive intensive farming systems (Luick, 1998;Körner, 1999). In particular, this last trend has been related with drastic changes in the ecosystem structure, such as shrub encroachment and forest recolonization (Lasanta-Martínez et al, 2005;Lasanta-Martínez et al, 2006), what in turn may increase fire events (Carcaillet et al, 2009), reduce biodiversity (Helm et al, 2006), and boost some forest animal populations beyond an equilibrium threshold (Laiolo et al, 2004).…”
Section: Introductionmentioning
confidence: 99%